Expression of paraoxonase 1 in HEK293 cells and its effect on lactonase and arylesterase activity in samples containing human serum and/or prooxidant or antioxidant agents - a preliminary study - Anna Bizoń; Agnieszka Piwowar (Polskie Towarzystwo Farmaceutyczne, 2023)
Expression of recombinant paraoxonase 1 (PON1) in the human embryonic kidney (HEK293F) cell line was evaluated. Two recombinant human PON1 proteins were investigated: PON1-Fc, which has an Fc-tag on its C-terminal, and His-PON1-Fc, which has an Fc-tag on its C-terminal and histidine on its N-terminal. The influence of high and low-density lipoproteins, copper ions, iron ions, and thiolactone homocysteine, on arylesterase and lactonase activities of PON1 in human serum was examined. Two activities of PON1, arylesterase and lactonase, were measured using earlier elaborated kinetic spectrophotometric method with temperature control at 37°C using the water thermostated cuvette holder. It was demonstrated that the HEK293F expression platform is useful for obtaining recombinant human PON1 protein. Also, addition of high-density lipoprotein increased serum arylesterase and lactonase activity of PON1 to a greater extent than the addition of PON1-Fc or HisPON1-Fc recombinant proteins. In contrast, the addition of high-density lipoprotein to samples containing PON1-Fc or His-PON1-Fc did not increase PON1 activities, while low-density lipoprotein, copper ions, and iron ions, depressed PON1 arylesterase and lactonase activity. Obtained results indicated that it may be advantageous to stimulate PON1 activities rather than supplement with endogenous PON1 protein and HDL, which could be an interesting direction for further study. Furthermore, the work has highlighted some potential research directions for the use of PON1 as a therapeutic molecules. Nevertheless, the study had some limitations and should therefore be treated as a preliminary study.